2009
DOI: 10.1098/rsbl.2009.0612
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolating non-target risk of Bt crops from laboratory to field

Abstract: The tiered approach to assessing ecological risk of insect-resistant transgenic crops assumes that lower tier laboratory studies, which expose surrogate non-target organisms to high doses of insecticidal proteins, can detect harmful effects that might be manifested in the field. To test this assumption, we performed meta-analyses comparing results for non-target invertebrates exposed to Bacillus thuringiensis (Bt) Cry proteins in laboratory studies with results derived from independent field studies examining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 7 publications
(9 reference statements)
1
99
0
Order By: Relevance
“…The general question of whether laboratory studies on transgenic insecticidal crops can be extrapolated to the field situation has been recently addressed by Duan et al (2010). They showed that indeed laboratory studies on GM crops show effects that are either consistent with, or more conservative than, those found in field studies, provided that ecologically relevant routes of exposure have been addressed properly.…”
Section: Methodological Strengthmentioning
confidence: 99%
“…The general question of whether laboratory studies on transgenic insecticidal crops can be extrapolated to the field situation has been recently addressed by Duan et al (2010). They showed that indeed laboratory studies on GM crops show effects that are either consistent with, or more conservative than, those found in field studies, provided that ecologically relevant routes of exposure have been addressed properly.…”
Section: Methodological Strengthmentioning
confidence: 99%
“…Papers must meet the following criteria to be included in the database: (i) involve a field crop species that has been genetically transformed to express one or more cry genes derived from Bacillus thuringiensis; (ii) measure effects of the transformed crop for compiling this information has been created to facilitate continuing study (Duan et al, 2008(Duan et al, , 2010Marvier et al, 2007;Naranjo, 2009;Wolfenbarger et al, 2008). When GE plants that express Cry proteins, including Cry1Ac cotton, were compared to control plants that were not treated with chemical insecticide there was a reduction in arthropod abundance, but when control plants are treated with insecticide arthropod abundance is significantly higher in GE plants expressing Cry proteins (Marvier et al, 2007;Naranjo, 2009Wolfenbarger et al, 2008.…”
Section: Field Studies Of Cry1ac On Non-target Organismsmentioning
confidence: 99%
“…As recently reported by Duan et al (2010), field studies with Coleopteran-active Cry proteins have either confirmed lab results or over- estimated the possible negative effects. In this view, our results confirm that, at least for the species selected, the use of GM tomato in the field has no appreciable effects on non-target pests and antagonists.…”
Section: Discussionmentioning
confidence: 57%